The no-flow phenomenon following drug-coated balloon angioplasty in a patient with chronic limb-threatening ischemia and a history of below-knee amputation. Issue 3 (March 2023) - Sobajima, Mituso; Imamura, Teruhiko; Fukuo, Atsuko; Ueno, Yohei; Onoda, Hiroshi; Ueno, Hiroshi; Kinugawa, Koichiro
Abstract: The endovascular treatment using a drug-coated balloon (DCB) reduces restenosis and target vessel re-vascularization rate in patients with peripheral artery disease such as claudication and chronic limb-threatening ischemia (CLTI). However, its safety and efficacy in patients with post-below-knee amputation remain unknown. We had a patient with CLTI and a history of below-knee amputation, who suffered a no-flow phenomenon following DCB angioplasty that required above-knee amputation. DCB angioplasty might not be appropriate for those with severe CLTI and histories of amputation. Learning objective: The present report describes the risk of endovascular treatment using a drug-coated balloon for chronic limb-threatening ischemia patients with a below-knee amputated limb.